1986
DOI: 10.3354/meps033131
|View full text |Cite
|
Sign up to set email alerts
|

Sinking rates of phytoplankton assemblages in the Weddell Sea marginal ice zone

Abstract: Sinhng rates of phytoplankton assemblages from the Weddell Sea marginal ice zone were measured during a cruise in November-December 1983. A homogeneous sample method (SET-COL) was used to measure sinking rates which permitted rates of various parameters of particulate matter to be determined simultaneously. Parameters assayed in this study included chlorophyll a. phaeophytin, biogenic silica, particulate carbon, particulate nitrogen, and for certain stations, numbers of diatoms. Sinking rates varied within eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
(24 reference statements)
2
21
1
Order By: Relevance
“…Therefore the duration of settling according to Bienfang (1981a) would not influence calculated sinking rates, provided trials were not run over sufficient duration to allow the settled fraction of the population to attaln unity, as such occurrence would yield an underestimate of the true sinking rate of the sample. Johnson & Smith (1986) agreed that this may be true for unialgal cultures. However, in natural systems with heterogeneous phytoplankton assemblages, differences in the sinking rates of the various particulates may result in differences in the calculated mean sinking rate of the assemblage, depending on the duration of the experiment.…”
Section: S T B S T B S T B S T B S T B S T B S T B S T B S T Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the duration of settling according to Bienfang (1981a) would not influence calculated sinking rates, provided trials were not run over sufficient duration to allow the settled fraction of the population to attaln unity, as such occurrence would yield an underestimate of the true sinking rate of the sample. Johnson & Smith (1986) agreed that this may be true for unialgal cultures. However, in natural systems with heterogeneous phytoplankton assemblages, differences in the sinking rates of the various particulates may result in differences in the calculated mean sinking rate of the assemblage, depending on the duration of the experiment.…”
Section: S T B S T B S T B S T B S T B S T B S T B S T B S T Bmentioning
confidence: 99%
“…Shorter settling times thus measure primarily the faster sinking fraction of the partlculates, whereas longer settling times give lower sinking rates, which result from the cumulative impact of slower sinlung particles. Johnson & Smith (1986) therefore suggested that the settled biomass fraction may be a hyperbolic function of the duration of settling.…”
Section: S T B S T B S T B S T B S T B S T B S T B S T B S T Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a relatively simple technique called SETCOL was developed to measure the sinlung rate of particulate matter in the field (Bienfang 1981a). This method has been frequently applied in various geographical regions with results revealing a dependency of sinking rate on phytoplankton cell size (Smayda & Bienfang 1983, Bienfang 1984, Jacques & Hoepffner 1984, ambient light intensity , Bienfang 1985, Johnson & Smith 1986, and nutrient concentrations (Bienfang 1981b, Bienfang et al 1982, Bienfang & Harrison 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, study of phytoplankton sinking rates is important for the comprehensive understanding of carbon sedimentation mechanisms of various phytoplankton communities, including different type of algal blooms (Johnson and Smith, 1986;Pitcher et al, 1989). Particle sinking rate can be calculated using the Stokes' law: ψ = 2 gr 2 (ρ P − ρ SW )/9η, where ψ is the sinking rate, g is gravitational acceleration, r is the spherical particle radius (m), ρ P is particle density, ρ SW is seawater density and η is dynamic viscosity (Happel and Brenner, 1991).…”
mentioning
confidence: 99%